Evaluation of metal-organic framework NH2-MIL-101(Fe) as an efficient sorbent for dispersive micro-solid phase extraction of phenolic pollutants in environmental water samples - Burakham, Rodjana (Elsevier, 2020)
This work proposes an application of amine-functionalized metal-organic framework (NH2-MIL-101(Fe)) as sorbent for dispersive micro-solid phase extraction (D-μSPE) of ten priority phenolic pollutants. The sorbent was simply synthesized under facile condition. The entire D-μSPE process was optimized by studying the effect of experimental parameters affecting the extraction recovery of the target analytes. The final extract was analyzed using high performance liquid chromatography with photodiode array detector. Under the optimum condition, the proposed procedure can be applied for wide linear calibration ranges between 1.25–5000 μg L−1 with the correlation coefficients of greater than 0.9900. The limits of detection (LODs) and limits of quantitation (LOQs) were in the ranges of 0.4–9.5 μg L−1 and 1.25–30 μg L−1, respectively. The precision evaluated in terms of the relative standard deviations (RSDs) of the intra- and inter-day determinations of the phenol compounds at their LOQ concentrations were below 13.9% and 12.2%, respectively. High enrichment factors up to 120 were reached. The developed method has been successfully applied to determine phenol residues in environmental water samples. The satisfactory recoveries obtained by spiking phenol standards at two different concentrations (near LOQs and 5 times as high as LOQs) ranged from 68.4–114.4%. The results demonstrate that the NH2-MIL-101(Fe) material is promising sorbent in the D-μSPE of phenolic pollutants.